Funtastic Game sebagai Upaya Meningkatkan Kemampuan Problem Solving pada Anak Usia Dini - Aspia, Ispi; Anggarasari, Nandhini Hudha (AS-SABIQUN, 2024)
Research on the use of scientific experimental techniques is discussed in this article in an effort to improve early life (4-5 years) problem-solving abilities. The aim of this research is to observe the initial condition of the problem-solving abilities of children aged here before being given action using the application of scientific experimental methods. This research was carried out in group A: (4–5 years) Nagarasari, Tasikmalaya City, RA Al-Mu'min. There were sixteen participants in the study: five girls and eleven boys. Classroom Action Research (CAR) conducted in three cycles is used for this kind of research. The first meeting was with the recovery reaction experiment, the second meeting was with the soap pepper touch experiment and the last meeting was with the experiment of knowing the process of rain. The instrument used was an observation sheet on the problem-solving abilities of early childhood. The results of children's learning achievements using this experimental method provide a better influence on the presentation of high levels of success.